Novel SNP Genotyping Assays Facilitate Species Identification of Salvelinus Collected in a Recreational Fishery. Issue 1 (6th January 2014) - DeHaan, Patrick W.; Pascal, Carita E.; Seeb, James E.
Abstract: Members of the genus Salvelinus often occur sympatrically, exhibit a high degree of phenotypic plasticity, and commonly hybridize. These factors often complicate species identification and hybrid detection based solely on morphology. Many species and populations of Salvelinus are threatened or endangered and accurate species identification and hybrid detection are important for conservation. Single nucleotide polymorphism (SNP) markers offer several advantages over other classes of genetic markers for species identification. We used DNA sequences from six species of Salvelinus to identify 16 SNPs that exhibited fixed differences among species and 16 additional SNPs that were variable within different species. These markers were used for species identification of putative Bull Trout Salvelinus confluentus that were misidentified as Lake Trout S. namaycush in a recreational fishery in Lake Pend Oreille, Idaho. The markers developed in this study will be useful for Salvelinus species identification and provide important data for conservation efforts.